2011
DOI: 10.5194/acp-11-215-2011
|View full text |Cite
|
Sign up to set email alerts
|

Inferring absorbing organic carbon content from AERONET data

Abstract: Abstract. Black carbon, light-absorbing organic carbon (often called "brown carbon") and mineral dust are the major light-absorbing aerosols. Currently the sources and formation of brown carbon aerosol in particular are not well understood. In this study we estimated the amount of light-absorbing organic carbon and black carbon from AERONET measurements. We find that the columnar absorbing organic carbon (brown carbon) levels in biomass burning regions of South America and Africa are relatively high (about 15-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
137
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(147 citation statements)
references
References 43 publications
(74 reference statements)
9
137
1
Order By: Relevance
“…(1). While the BC AAE = 1 assumption has been generally accepted as a means to estimate BC absorption contribution (e.g., Clarke et al, 2007;Yang et al, 2009;Arola et al, 2011), studies have shown variability in BC AAE (e.g., Lack and Cappa, 2010). For instance, Lack and Cappa (2010) found that, for BC mixtures and BC containing coatings, BC AAE can be as high as 1.6.…”
Section: Contribution Of Oa To Spectral Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1). While the BC AAE = 1 assumption has been generally accepted as a means to estimate BC absorption contribution (e.g., Clarke et al, 2007;Yang et al, 2009;Arola et al, 2011), studies have shown variability in BC AAE (e.g., Lack and Cappa, 2010). For instance, Lack and Cappa (2010) found that, for BC mixtures and BC containing coatings, BC AAE can be as high as 1.6.…”
Section: Contribution Of Oa To Spectral Absorptionmentioning
confidence: 99%
“…To investigate the influence of OA on spectral absorption for the 17 April and 29 June biomass burning plumes, spectral (350-500 nm) b abs,λ attributed to OA (b abs, OA,λ ) was estimated using previously established methods Yang et al, 2009;Arola et al, 2011). First, spectral b abs,λ due to BC (b abs,BC,λ ) was determined by assuming BC dominated the PSAP absorption at 660 nm.…”
Section: Contribution Of Oa To Spectral Absorptionmentioning
confidence: 99%
“…For most compounds, especially OC, RI decreases with wavelength (Table 4), but on several occasions AERONET RI increases with wavelength, which leads to discrepancies between modeled and observed aerosol optical properties, especially at 440 nm. Since IRI strongly increases towards the ultraviolet wavelengths for OC, contrary to that of BC (Jacobson, 1999;Kirchstetter et al, 2004;Sun et al, 2007;and Chen and Bond, 2010), this hampers the method's ability to distinguish black carbon from absorbing organic matter ("brown carbon") (e.g., Bergstrom et al, 2007;Russell et al, 2010;Arola et al, 2011).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The relative fractions of Level 2 data out of our selected set from Level 1.5, for refractive in- dices, were about 60, 97, 85, and 88 % for Karachi, Lahore, Kanpur, and Gandhi College, respectively. Schuster et al (2005) developed an approach to retrieving black carbon concentration and specific absorption from AERONET retrievals of imaginary refractive indices, and it was further extended by Arola et al (2011) to also include BrC. Recently, this method was further extended by Schuster et al (2015a) to simultaneously include carbonaceous aerosols (both BC and BrC) and also mineral dust in both fine and coarse modes separately.…”
Section: Aeronet Datamentioning
confidence: 99%